Las leyes de tercero excluido y contradicción como valores límite en lógica difusa - Salazar Morales, Omar; Soriano Méndez, José Jairo (Ingeniería, 2011)
This paper presents the study of the laws of excluded middle and contradiction of classical logic in fuzzy logic because in the latter, in general, are not satisfied. The aim is to present the conditions under which these two laws as limit values are met with the correct choice of the fuzzy logical operators.